Incidence and risk factors of venous thrombotic events in pediatric patients with CNS tumors compared with non-CNS cancer: A population-based cohort study. Issue 200 (April 2021) - Howie, Chelsea; Erker, Craig; Crooks, Bruce; Moorehead, Paul; Kulkarni, Ketan
Abstract: Background: Venous thromboembolism (VTE) is a well-recognized complication in pediatric cancer patients. It has been demonstrated that the incidence of VTE in pediatric patients with central nervous system (CNS) tumors is lower than that of patients with other cancers. Risk factors for developing cancer-related thrombosis are numerous and can include patient, disease, or treatment-related influences. The present study was designed to assess the VTE incidence in a pediatric oncology population, and to investigate whether intensity of treatment has similar associated with risk of VTE development in patients with and without CNS tumors. Methods: A retrospective population-based cohort study of pediatric oncology patients in Atlantic Canada was conducted. Data collected from medical records included demographics, cancer type, treatment, presence of central venous catheters (CVC), and presence of thrombosis. Treatment intensity was assessed using the intensity of treatment rating scale (ITR-3). Study period was from January 2000 to December 2017. SPSS version 24 was used for statistical analysis. Results: Of 1262 patients with pediatric cancer, 247 (19.6%) had CNS tumors. VTE occurred in significantly fewer (n = 5, 2%) patients with CNS tumors compared with patients with non-CNS cancers (n = 79, 7.8%) ( p = 0.001). The ITR-3 scores did not differ significantly between the CNS and non-CNS groups ( p = 0.638). In a multivariate logistic regression analysis, ITR-3 score was associated with VTE (odds ratio [OR]: 1.48, 95% CI: 1.2–1.9), while presence of CNS tumor was protective (OR: 0.26, 95% CI: 0.1–0.6). Conclusions: We demonstrate that pediatric patients with CNS tumors experience a significantly lower incidence of VTE compared with patients with non-CNS cancer. An increase in the ITR-3 rating significantly increased the odds of developing VTE. Highlights: Significantly lower incidence of thrombosis among pediatric brain tumor patients Similar treatment intensity between pediatric brain tumors and other cancers Higher ITR-3 scores are associated with higher risk of thrombosis development.